ABOUT SOME UNFOLVED PROBLEMS OVERCOMING DOMESTIC VIOLENCE - Ланцедова, Юлія Олександрівна; Літвінова, Ірина Феофанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to substantiate some options for improving the means of overcoming domestic violence. Research methods: comparative-legal analysis, cognitive-analytical, etc. Result: the differentiation of violence and direct and delegated state coercion, improvement of legislative definitions of domestic violence and its types. Discussion: it has been established that in recent years the urgency of solving the problems associated with domestic violence has sharply increased, especially in the conditions of the all-Ukrainian quarantine. The reason for this need lies in the significant leap towards an increase in the number of cases of domestic violence. This state of affairs is facilitated by a large number of shortcomings in the relevant recommendations of international partners, Ukrainian legislation and practice. It was emphasized that it is advisable to supplement the legislative definitions of the concept of domestic violence and each of its types with the words: «in the absence in the act of signs of direct or delegated to the family, labor, educational or other collective, or the socio-environment of state coercion, which has an inextricable set of basic legal signs of its legitimacy: necessity. sufficiency, humanity, professionalism, balance) and/or circumstances precluding antisociality or guilt of this act (necessary defense, imaginary defense, extreme necessity, justified risk, detention of the offender, mental or physical coercion)». In order to completely eliminate the contradictory concept of sexism that has arisen in connection with the introduction of the recommendations of the Committee of Ministers of the Council of Europe, which has intermixed all sex-based offenses, and therefore does not provide an opportunity to most effectively, rationally and qualitatively implement the process of overcoming domestic violence, based on traditional sexual offenses and violations of other sexual characteristics.